THE IMPACT OF FINTECH ON THE SUSTAINABILITY OF ISLAMIC ACCOUNTING AND FINANCE EDUCATION IN MALAYSIA - Nurul Nazlia Jamil; Junaidah Abu Seman (Journal of Islamic, Social, Economics and Development, 2019)
In a recent survey conducted by PricewaterhouseCoopers (PwC) on Global Banking and Capital Markets (BCM), a vast majority of CEOs (93%) identified technology changes as a key contributor to transforming the sector over the next five years. The financial services sector must be able to respond to this transformation and therefore, will require labour talent that combines strong financial and digital skills. Through this report, the study explore the financial technology (Fintech) industry to understand how the industry and educational institutions have responded to the increasing need for sustaining the Islamic finance curriculum and improving the talents. The objective of this research is twofold; first, the research turns to highlight Malaysia responses on the role of fintech in sustaining the education and the issues of talent shortages. The responses have been categorized into three primary themes: (1) Educational Interventions, (2) Incubators and Extra-Curricular Events; and (3) Government and Policy Interventions. Secondly, the research consolidates and reframes the discussion by acknowledging that multiple opportunities for improvement exist within Malaysia’s Islamic Fintech ecosystem, helping to identify a series of suggestions that could be considered by the local industry and education institutions.